A student solved the equation: x + 2 (x + 1) = 17

Line 1: x + 2x + 1 = 17
Line 2: 3x + 1 = 17
Line 3: 3x = 16
Line 4: x = 16/3

1 answer

Let's analyze the student's solution step by step:

The original equation is: \[ x + 2(x + 1) = 17 \]

Line 1: Expand the equation

The student rewrote it as: \[ x + 2x + 2 = 17 \] This step includes distributing the 2 in \( 2(x + 1) \) properly:

The correct expansion should be: \[ x + 2x + 2 = 17 \]

Line 2: Combine like terms

The student then combined like terms: \[ 3x + 2 = 17 \]

Line 3: Solve for \( x \)

Next, they subtracted 2 from both sides: \[ 3x = 17 - 2 \] \[ 3x = 15 \]

Line 4: Finally, solve for \( x \)

Now, divide by 3: \[ x = \frac{15}{3} \] \[ x = 5 \]

Conclusion

The student's final answer \( x = \frac{16}{3} \) is incorrect. The correct solution to the equation \( x + 2 (x + 1) = 17 \) should yield \( x = 5 \).